Parameterizing the Wind-Wave Relation with or Without Fetch Parameter for Marine Science and Engineering - Shih-Ang (S.. A.) Hsu (Universitas Airlangga, 2026)
In the realm of wind and wave interaction, traditionally, nearly all coastal and marine scientists and engineers have used the JONSWAP wave spectra which contains a variable called the “Fetch Parameter, X”. Since it is a challenge to determine this parameter objectively, most recently, this author has proposed an alternative method to link the wind speed at 10-m, U10 to the significant wave height, Hs. All units employed in this study are in SI. In this short communication, we first demonstrate in the Introduction that one needs caution to apply the wind-wave relation containing the fetch parameter. Then, based on the simultaneous measurements of the wind speed at 10-m, U10 (up to 72 m s -1) and the significant wave height, Hs (up to 27.6 m), during Hurricane Lili and Super-Typhoon Soudelor, the fetch parameter, X in km, used in the JONSWAP wave spectra is found to be X 0.5 = 5.5Ln (Hs) + 7.4 with a correlation coefficient, R = 0.90, so that U10 = 61Hs/(5.5Ln(Hs) + 7.4). Comparing this proposed formula for the wind-wave relation with the fetch parameterization against a relation without fetch parameter in the literature, i.e., U10 = 2.33Hs + 6, indicates that there is nearly no difference. However, further analysis based on simultaneous measurements of U10 and Hs without X during six hurricanes shows this formula is useful for air-sea interaction studies including the estimation of overwater friction velocity and wind stress determination to bypass the use of the drag coefficient which varies greatly.